Dihydroergotamine and triptan use to treat migraine during pregnancy and the risk of adverse pregnancy outcomes - Anick Bérard (Nature Portfolio, 2021)
Abstract Migraine is prevalent during pregnancy. Antimigraine medications such as dihydroergotamine (DHE) and triptans have been associated with adverse pregnancy outcomes in individual studies but lack of consensus remains. We compared the risk of prematurity, low birth weight (LBW), major congenital malformations (MCM), and spontaneous abortions (SA) associated with gestational use of DHE or triptans. Three cohort and one nested-case–control analyses were conducted within the Quebec Pregnancy Cohort to assess the risk of prematurity, LBW, MCM, and SA. Exposure was defined dichotomously as use of DHE or triptan during pregnancy. Generalized estimation equations were built to quantify the associations, adjusting for potential confounders. 233,900 eligible pregnancies were included in the analyses on prematurity, LBW, and MCM; 29,104 cases of SA were identified. Seventy-eight subjects (0.03%) were exposed to DHE and 526 (0.22%) to triptans. Adjusting for potential confounders, DHE and triptans were associated with increased risks of prematurity, LBW, MCM, and SA but not all estimates were statistically significant. DHE was associated with the risk of prematurity (aRR: 4.12, 95% CI 1.21–13.99); triptans were associated with the risk of SA (aOR: 1.63, 95% CI 1.34–1.98). After considering maternal migraine, all antimigraine specific medications increased the risk of some adverse pregnancy outcomes, but estimates were unstable.